KAZAKHSTAN GERMANS: TRAGICAL PAGES OF HISTORY - Kalybekova M.Ch.; Apendiyev T.A. (Scientific Journal of Pedagogy and Economics, 2020)
At present, the peoples of Kazakhstan, as well as the entire post-Soviet space are undergoing spiritual awakening and a return to traditional sources. It is important that the processes of searching for national identity are a universal historical and sociocultural tendency of the modern world. In domestic historical science for a long time there has been a steady interest in the formation of the multi-ethnic composition of the population of history. One of the representatives are Germans. Deportation, as a large-scale action of the state to some peoples inhabiting its territory, including Germans, as a phenomenon of recent history, the consequences of which are tangible to this day should be analyzed and evaluated from the point of view of not only historical-political, moral, but also legal criteria. Based on archival documents and materials, for the concept of Stalinist stereotypes caused primarily by understanding the causes, main trends, scale, consequences of the government’s repressive measures against the Germans of Kazakhstan. The study of the economic structure and labor mobilization of the Germans allows us to trace the role of special settlers in creating a powerful industrial potential of the country in remote areas with severe climatic conditions. And of particular interest is the question of the work of state authorities to create the living conditions of special German resettlers in special settlements, the problems of the legal status of special resettlers, the removal of restrictions on legal provisions, the repatriation of Germans.